Pengembangan Game Edukasi Web EcoSort: City Savior untuk Pemilahan Sampah Rumah Tangga - Vebby Ardita Manalu; Benny Pinontoan; Christian A.J. Soewoeh; Mahardika Inra Takaendengan (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
Household waste management remains an environmental challenge due to limited public understanding regarding waste classification. This study aims to develop a web-based 2D educational game entitled EcoSort: City Savior and evaluate changes in users’ knowledge after using the game. The system was developed using the Game Development Life Cycle (GDLC) method and implemented using Unity 2D with WebGL technology. Functional testing was conducted using Black-Box Testing with the Equivalence Partitioning technique. The evaluation applied a one-group pretest–posttest design involving 30 respondents aged 15–17 years. The results showed that the average pretest score increased from 41 to 88 in the posttest. Statistical analysis using the paired sample t-test produced a p-value of 4.39272E-13 (p < 0.05), indicating a significant difference between pretest and posttest scores. These findings indicate that EcoSort: City Savior has the potential to be used as an interactive learning medium for improving understanding of household waste classification.